Hubungan hipertensi dengan fungsi kognitif di Poliklinik SMF Ilmu Penyakit Dalam RSUP Prof. Dr. R. D. Kandou Manado - Pandean, Gloria V.; Surachmanto, Eko E. (e-CliniC, 2016)
Abstract: Hypertension is an increase in blood pressure above normal. It is categorized as a silent disease because people do not know whether they suffer from hypertension or not until their blood pressures were checked. This study aimed to obtain the relationship between hypertension and cognitive function. This was an analytical study with a cross sectional design. Subjects were adult hypertensive patients who came to the Clinic of Internal Medicine Department Prof. Dr. R. D. Kandou Hospital Manado. The results showed that there were 45 patients as subjects consisted of 20 males and 25 females. There was a tendency that the higher systolic or diastolic blood pressure, the lower the cognitive function. Among patients with hypertension â‰¥5 years there was a highly significant relationship between duration of hypertension and impaired cognitive function. According to MMSE results of cognitive function, there were 27 patients with normal cognitive function, 2 patients with moderate impairment, and 16 patients with mild impairment. There was no cases of severe disorder.Keywords: hypertension, cognitive functionAbstrak: Hipertensi adalah suatu keadaan dimana terjadi peningkatan tekanan darah di atas normal pada pemeriksaan tekanan darah. Penyakit ini dikategorikan sebagai the silent disease karena penderita tidak mengetahui dirinya mengidap hipertensi sebelum memeriksakan tekanan darahnya. Penelitian ini bertujuan untuk mengetahui apakah terdapat hubungan antara hipertensi dan fungsi kognitif. Jenis penelitian ini analitik dengan desain potong lintang. Sampel ialah pasien dewasa penyandang hipertensi yang datang ke Poliklinik SMF Ilmu Penyakit Dalam RSUP Prof. Dr. R. D. Kandou Manado. Jumlah sampel 45 orang terdiri dari 20 laki-laki dan 25 perempuan. Hasil penelitian memperlihatkan terdapat kecenderungan semakin tinggi tekanan darah sistolik (TDS) dan tekanan darah diastolik (TDD) maka semakin rendah fungsi kognitif. Pada penyandang hipertensi selama â‰¥5 tahun terdapat hubungan yang sangat signifikan antara durasi menyamdang hipertensi dan gangguan fungsi kognitif. Hasil pemeriksaan MMSE mendapatkan 27 pasien dengan fungsi kognitif normal, 2 pasien dengan gangguan kognitif derajat sedang, dan 16 pasien dengan derajat ringan; tidak terdapat pasien dengan gangguan kognitif derajat beratKata kunci: hipertensi, fungsi kognitif